(untitled) (k:ON - Kölner Online Journal für Lehrer*innenbildung, 2026)
This article expands on the existing LRT initiative in two ways. First, it focuses on vulnerable language learners with developmental language disorders and the particular challenges they face. Their case shows how linguistic risks can arise in the context of first language acquisition and how healthy linguistic risk-taking can possibly support communicative participation and language development. Second, this article summarizes the extensive resilience research conducted over the past decades and concludes with an initial conceptualization of communicative resilience, thereby attempting to provide new impetus to the LRT initiative.